THE INFLUENCE OF MEDIA LITERACY ON THE CULTURE OF CRITICAL THINKING (Heritage, 2022)
Digital technologies affect the way of life of both individuals and the modern society as a whole. Active participation on social networks directs us to frequent connections with social media. However, the field of electronic media is often a platform for sharing content that does not aim to place true information, but to influence public perception. In order for media users to be able to recognize the goal of media information, it is necessary for them to master knowledge and competencies. Media literacy plays a key role in this. The goal we set in this paper is to determine to a what ectent media literacy is recognized and what is the perception of respondents about how knowledge / ignorance of media literacy affects the culture of critical thinking and willingness of media users to accept cultural diversity. The paper presents a part of the research conducted by the author during 2021, the part related to the impact of media literacy on the goal set in this paper, and presents the results which confirm that a higher degree of mastery of media literacy competencies has a positive effect on a culture of critical thinking, and that a more developed critical capacity to assess information and the media provides a greater opportunity for media users to embrace cultural diversity.
Keywords: digital technologies, media literacy, culture of critical thinking, cultural diversity